Saridin Mokong Karya Sucipto Hadi Purnomo Sebagai Respons Pembaca - Jannah, Raundoh Tul; Nugroho, Yusro Edy (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
Saridin Mokong is a Javanese serialized story of the Pati dialect resulting from literary reactualization from several sources such as Sri Kencono's Audio Kethoprak, the